From the History of Corporate Mercenarism: British Clandestine Operation in the North Yemen in 1960s - M. A. Nebolsina (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The situation in Yemen in the 1960s went far beyond an ordinary public upheaval and internal crisis. The turmoil caused by the political regime change affected the interests of numerous foreign stakeholders, in particular, of Great Britain. The response of the British government to a new threat to its strategic interests in the region took form of a mercenary operation. An unofficial use of mercenaries for clandestine operations was not an extraordinary measure in the modern world history. However, the British operation in Yemen stands out in that regard as it was for the first time since the end of the World War II that such mission was carried out by mercenaries alone. It is therefore not surprising that this operation has played a crucial role in the development of corporate mercenarism in general.The first section examines the causes and triggers of Great Britain’s intervention in the North Yemen Civil War in both global and regional contexts. The second section covers the initial stage of the mercenary operation: its priorities and objectives, funding mechanisms, the main forms and the role of mercenaries’ assistance to the Royalist forces. The author also emphasizes the role of regional actors, involved in the conflict on both sides: that of the Republican government (Egypt) and that of the former royal regime (Saudi Arabia, Israel). Finally, the third section examines the mercenary activities in the final stages of the North Yemen Civil War, particularly difficulties they faced as the British and the Saudi governments began to lose interest in supporting the Royalists. In conclusion the author assesses the influence of this operation on the development of corporate mercenarism.